RIBS@UA: interface to collect and store respiratory data, a preliminary study - Pinho, Cátia (2018)
Objectives: The development of effective graphical user interfaces (GUIs) has been in an emergent demand in healthcare technologies, for assessing, managing and storing patients’ clinical data. Nevertheless, specifically for respiratory care there is a lack of tools to produce a multimedia database, where the main respiratory clinical data can be available in a single repository. Therefore, this study reports on the development of a usable application to collect, organise and store respiratory-related data in a single multimedia database. Methods: A GUI, named RIBS@UA, organised in a multilayer of windows was developed in MATLAB and evaluated. The evaluation consisted of usability inspection (by two respiratory health professionals and two system designers during the development of the prototype) and usability testing (by seven physiotherapists). Results: The users reported on the utility of the new application and its potential to be used in clinical/research settings. It was also stated that RIBS@UA facilitates diagnosis/assessment and contributes to the implementation of standardised interventions and treatment procedures. Nevertheless, some drawbacks were identified and suggestions were given to improve the content of specific features in the physiotherapy sessions window. Conclusions: RIBS@UA interface is an innovative application to collect, store and organise the main respiratory-related data, in a single multimedia database. Nevertheless, further improvements are still recommended before the final implementation of RIBS@UA.